2021
DOI: 10.1186/s12884-021-03597-9
|View full text |Cite
|
Sign up to set email alerts
|

A validation of the Postpartum Specific Anxiety Scale 12-item research short-form for use during global crises with five translations

Abstract: Background Global crises inevitably increase levels of anxiety in postpartum populations. Effective and efficient measurement is therefore essential. This study aimed to create a 12-item research short form of the 51-item Postpartum Specific Anxiety Scale [PSAS] and validate it for use in rapid response research at a time of global crises [PSAS-RSF-C]. We also present the same 12-items, in five other languages (Italian, French, Chinese, Spanish, Dutch) to increase global accessibility of a psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 44 publications
3
43
0
1
Order By: Relevance
“…The factor structure of the PSAS (Table 2) was assessed using all the participants in sample 1 (n = 672). First, the parallel analysis suggested there were four factors which is consistent with the original 51-item measure (Fallon et al 2016) and the 12-item crisis short-form (Silverio et al 2021). The PCA demonstrated that the sampling adequacy for the scale was excellent (KMO = 0.95) and Bartlett's test of sphericity indicated sufficient correlations for PCA (χ 2 (1275) = 15,634.93, p < .001).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The factor structure of the PSAS (Table 2) was assessed using all the participants in sample 1 (n = 672). First, the parallel analysis suggested there were four factors which is consistent with the original 51-item measure (Fallon et al 2016) and the 12-item crisis short-form (Silverio et al 2021). The PCA demonstrated that the sampling adequacy for the scale was excellent (KMO = 0.95) and Bartlett's test of sphericity indicated sufficient correlations for PCA (χ 2 (1275) = 15,634.93, p < .001).…”
Section: Resultsmentioning
confidence: 60%
“…A common consequence of creating short-form measures is reduced psychometric qualities in comparison to their original counterparts due to the fact that there are fewer items measuring the construct (Widaman et al 2011). While the PSAS offers a more detailed assessment of anxiety, the PSAS-RSF performed comparably well to its parent form and reduces potential response burden, particularly when used alongside a battery of measures or in a health care setting (see also PSAS-RSF-C; Silverio et al 2021). Furthermore, the original…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After gaining the necessary permissions from the PSAS working group, the original version was translated from English into Persian using approved translation methods [ 21 ]. This was done by a native translator with good command of the Persian language.…”
Section: Methodsmentioning
confidence: 99%
“…For example, fear of contracting the virus and its consequences presented a particular worry for pregnant women, who were initially considered more 'vulnerable' to COVID-19 than the general population [30][31][32][33] Furthermore, women faced uncertainty around perinatal care [5,32,34,35], Health Visitors were redeployed in some parts of the UK, and many families reported not experiencing the perinatal care that they had expected [35,36]. Lockdown instigated to limit transmission of the virus resulted in extended periods of physical and social isolation, preventing access to many forms of support, and leaving co-parents excluded from attending antenatal appointments or visiting mothers during postpartum hospital admissions [28,32,34,37].…”
Section: Introductionmentioning
confidence: 99%